Unveiling the mechanism of photothermal therapy in acne man-agement: targeting sebaceous gland ferroptosis via umbilical cord mesenchymal stem cell membrane-encapsulated Au-Ag-PDA - Wu, Ronghui; Li, Jing; Tian, Hao; Song, Dandan; Zhao, Tianqi; Tian, Yangyang; Zouboulis, Christos C.; Jiang, Jinlan; Zhu, Mingji (Frontiers in Bioengineering and Biotechnology, 2024)
Background Branched gold and silver nanoparticles coated with polydopamine (Au-Ag-PDA) demonstrate high photothermal conversion efficiency. Utilizing umbilical cord mesenchymal stem cell membranes (MSCM) as an effective drug delivery system, our preliminary studies investigated the suppression of sebum secretion in sebaceous glands using MSCM-coated Au-Ag-PDA nano-particles (Au-Ag-PDA@MSCM) combined with 808 nm laser irradiation, showing potential for dermatological applications in acne treatment. Methods This study employs proteomic analysis, complemented by subsequent techniques such as Western blotting (WB), small interfering RNA (siRNA), and transmission electron microscopy, to further investigate the differential mechanisms by which Au-Ag-PDA and Au-Ag-PDA@MSCM-mediated photothermal therapy (PTT) suppress sebum secretion. Results Our proteomic analysis indicated mitochondrial respiratory chain damage in sebaceous gland tissues post-PTT, with further validation revealing ferroptosis in sebaceous cells and tissues. Acyl-CoA Synthetase Long-Chain Family Member 4 (Acsl4) has been identified as a critical target, with Au-Ag-PDA@MSCM demonstrating enhanced ferroptotic effects. Conclusion These findings significantly advance our understanding of how PTT mediated by Au-Ag-PDA@MSCM nanoparticles reduces sebum secretion and underscore the pivotal role of MSCM in inducing ferroptosis in sebaceous glands, thus providing a robust theoretical foundation for employing PTT via specific molecular pathways in acne treatment.